Review on the fundamental usage of Bills of Quantities (BQ) by contracting organisations - Bandi, Shamsul Hadi; Abdullah, Fadhlin; Amiruddin, Roslan (University Technology Sydney Press, 2014)
Detail literature review indicates a growing concern over the purpose of the BQ to the practice and needs of contracting organisations. However, the number of studies dedicated to comprehensively review how BQ is used by these organisations is limited. This review is conducted with the aim to identify the fundamental usage of BQ to contracting organisations; especially within the parameter of a project period and management functions. The main three objectives are: (1) to comprehensively identify relevant literature concerning the usage of BQ to contracting organisations, (2) to review the literature in order to identify the usage of BQ to contracting organisations, and (3) to systematically synthesize the outcome of the review in order to identify the fundamental usage of BQ to contracting organisations. Various literature findings are reviewed and validated to support the study’s outcome. As a result, this study manage to identify thirty fundamental usage of BQ arranged according to the parameter of interest. The significance of this study supports the evident usage of BQ by contracting organisations. It further enhances the current knowledge pertaining to its application in the industry and advancing further research pertaining on the application of BQ in the construction industry.